The domain expert perspective: A qualitative study into the views expressed in a standard-setting exercise on a language for specific purposes (LSP) test for health professionals. (January 2022) - Davidson, Simon
This paper investigates what matters to medical domain experts when setting standards on a language for specific purposes (LSP) English proficiency test: the Occupational English Test's (OET) writing sub-test. The study explores what standard-setting participants value when making performance judgements about test candidates' writing responses, and the extent to which their decisions are language-based and align with the OET writing sub-test criteria. Qualitative data is a relatively under-utilized component of standard setting and this type of commentary was garnered to gain a better understanding of the basis for performance decisions. Eighteen doctors were recruited for standard-setting workshops. To gain further insight, verbal reports in the form of a think-aloud protocol (TAP) were employed with five of the 18 participants. The doctors' comments were thematically coded and the analysis showed that participants' standard-setting judgements often aligned with the OET writing sub-test criteria. An overarching theme, 'Audience Recognition, ' was also identified as valuable to participants. A minority of decisions were swayed by features outside the OET's communicative construct (e.g., clinical competency). Yet, overall, findings indicated that domain experts were undeniably focused on textual features associated with what the test is designed to assess and their views were vitally important in the standard-setting process.